Implementation of Minister of Environment Regulation Number 7 of 2014 in The Implementation of Additional Criminal For Corporations That Commit Environmental Crime - Aqil, Nabil Abduh; Syahrin, Alvi; Triana, Wessy (Ikatan Penulis Mahasiswa Hukum Indonesia Law Journal, 2024)
The implementation of PERMEN-LH Number 7 of 2014 as a legal basis for imposing additional penalties for corporations raises problems because the related regulations have weaknesses in implementation, such as: aspects of legal synchronization, overlapping authority, potential legal consequences in the form of lawsuits against unlawful acts and uncertainty in determining the extent of the affected area due to criminal acts that affect the amount of costs incurred by corporations as additional penalties. The purpose of this study is to find out and analyze To find out and analyze the implementation of the Minister of Environment Regulation Number 7 of 2014 in several environmental criminal cases. To find out and analyze the legal consequences in the Minister of Environment Regulation Number 7 of 2014 on the enforcement of environmental criminal law in Indonesia. Additional penalties as in Article 119 UUPPLH do not have detailed implementing rules regarding the mechanism of its application. PERMEN-LH Number 7 of 2014 which is often used by law enforcement officials in environmental cases has weaknesses such as: not in sync with Article 119 of Law Number 32 of 2009 concerning Environmental Protection and Management; there is an overlap of authority between the Ministry of Finance and the Ministry of Environment and Forestry in terms of environmental restoration; and lack of certainty in calculating the extent of the affected area due to criminal acts. The imposition of additional penalties in the form of repairs due to criminal acts that are converted into a sum of money in Decision Number 256 / Pid.sus / PN Rgt; Case Number: 37 / Pid.Sus-LH / 2018 / PN; Case Number 349 / PID.B-LH / 2019 / PN.Plw has not been able to provide protection for the environment because it is considered non-tax state revenue (PNBP), which is entirely deposited into the State Treasury, thus the funds cannot be used as restoration or environmental improvement funds